Merdeka Belajar Kampus Merdeka: Program Magang Mahasiswa Sebagai Upaya Mencetak Sumber Daya Manusia Unggul Dan Berdaya Saing - Hanung Eka Atmaja Hanung; salfia putri dewina santri salfia (Publikasi Indonesia, 2022)
Merdeka Learning Program Merdeka Campus, especially student internships as a step to gain knowledge, experience, know and know the professional world or the real work system of the professional world. The concept of superior HR is superior performance, competitiveness, skill and quality. The Ministry of Education and Culture (Kemendikbud) has intensified eight Merdeka Learning programs, one of which is the Independent Campus Internship, which attracts students to take part. This internship is an off-campus learning activity that involves students, institutions or universities as well as industry. The subjects in this study were students of the Management Study Program, Faculty of Economics, State University No. The variables in this study were the MBKM Internship Program (X) and Superior and Competitive HR (Y). The author uses quantitative methods using descriptive research methods to describe the results of the research carried out. In this study the authors used a questionnaire as a tool to collect data. Then the data obtained were analyzed using the validity test, reliability test, normality test, simple linear regression analysis, t test (partial) and determinant test with the help of IBM SPSS version 25. The results showed that based on the results of the t test (partial) the variable t value was obtained. Excellent and Competitive HR (X) is 4,511 with a significant value of 0.000, which is smaller than 0.05. So it can be concluded that the MBKM Internship Program variable (X) has a significant positive effect on the Superior and Competitive HR variable (Y). Based on the determinant test, it can be seen that the value (Adjusted R Square) is 0.356, so the contribution of the influence of the MBKM Internship Program independent variable (X) on the Superior and Competitive HR variable (Y) in simple linear regression is 35.6% while the remaining 64.4% is influenced by factors others that were not investigated in this study. From the results of the analysis conducted by researchers, it can be concluded that there is an influence of the MBKM Internship Program on the achievement of Superior and Competitive Human Resources.